Complex DNA viruses: herpes virus - Blaho, John (Henry Stewart Talks, 2007)
Introduction to human herpes viruses, Common characteristics, Herpes virus replication, Attachment/penetration, Gene expression/cascade regulation, DNA synthesis, Assembly and packaging, Viral budding, Evasion of the immune response, Herpes virus pathogenesis, Cytopathic effect, HSV and VZV diagnosis, treatment and control
Archived at 2017/09/14